KARAKTERISASI DAN IDENTIFIKASI BAKTERI DARI TAMBA DAGING BABI (Sus sp.) HASIL FERMENTASI SPONTAN - Yana, Nova Yanti Dami; Dharma, Bodhi; Nugroho, Rudy Agung (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
This The aims of the study was to determine the bacteria which grown in fermented of the tamba pork (Sus sp.), the Dayak Bulusu traditional food. Descriptive analysis methods was used in the research. Isolation of bacteria were performed at 10-1 to 10- 10 dilution using NaCl solution. The cells mixture were poured and incubated at 37oC for 24 hours. Characterization of bacteria was done in basis of morphology of colony, Gram- staining, and a partial biochemical tests. Three strains of bacteria were isolated i.e. Pseudomonas, Staphylococcus and Klebsiella, respectively.